Implementation of Augmented Reality (AR) Learning Media on Learning Comprehension of Ship Safety Device Introduction - M Masrupah; Endang Lestari; Indra Farman; Dzakiyah Ulya (Journal of Science and Education (JSE), 2026)
The development of digital technology brings major changes in the world of education, including the maritime sector. One of the relevant and potential technologies is Augmented Reality (AR), which can integrate virtual objects into the real world in real-time, thus providing an immersive and interactive learning experience. This study aims to implement AR-based learning media introducing ship safety devices, such as life jackets, ring buoys, lifeboats, and fire extinguishers, and measure its effectiveness compared to conventional methods. The research method used a quantitative approach with a quasi-experimental design (pretest-post test control group design). The research sample was fourth semester Nautical students at Makassar Polytechnic of Shipping Science (PIP), with the division of experimental groups using AR and control groups using conventional methods. The results showed a significant increase in students' understanding of ship safety devices. The average score increased from 58.49 (pretest) to 66.94 (post test). The Wilcoxon Signed Ranks test result-ed in a p value = 0.003 (p < 0.05), which confirms the effectiveness of AR in improving learning outcomes. This finding shows that AR not only helps visualize abstract concepts to be more concrete but also increases student motivation and engagement. This study recommends the use of AR as a learning media innovation in the maritime field, while encouraging the development of broader, collaborative, and sustainable interactive content.